Protection or Silencing? Student Participation in Protest and The Future of Civil Society - Mohamad Rian Ari Sandi; Rahmat; Syaifullah (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2026)
The wave of demonstrations involving massive student participation has raised a fundamental dilemma between child protection and the participation right. This research analyzes the paradox of government policies that disguise the prohibition on student demonstrations under the guise of child protection, despite the UN Convention on the Rights of the Child (1989) recognizing both protection and participation rights as equally binding obligations of the state. This research looks at what the government's doing and how it affects students. It uses information from documents, laws, and science journals. The research found three things. First, the government is being too harsh. It does not understand what students need. It thinks that keeping students quiet is the same as keeping them safe. Second, look at what happened in Soweto in 1976 and with the Fridays for Future movement; we can see that student movements can bring about changes. The Soweto movement helped end the treatment of students during apartheid, and Fridays for Future changed the way people think about climate change. These movements are similar to student movements in Indonesia. They are facing resistance from institutions, but they are working together and making a difference. Third, the government's harsh policies are not stopping student movements. Instead, these policies might be hurting the country's ability to pass on values to the next generation. If the government does not start letting students participate and learn about being citizens in a safe way, it could hurt the country's ability to have a strong civil society.